The Effectiveness of Prayer Training on Perceived Stress of Women Heading Households Supported by Imam Khomeini Relief Foundation - Ali Sheykholeslami; Masoomeh Parsa (Shahid Beheshti University of Medical Sciences, 2019)
For downloading the full-text of this article please click here. Background and Objective: Women who head households constitute one of the most vulnerable groups in the society. They are exposed to social discrimination and psychological pressures more frequently than other groups of women. The purpose of this study was to investigate the effectiveness of prayer on perceived stress of women heading households supported by Imam Khomeini Relief Foundation. Method: A pretest-posttest design with control group was adopted in this quasi-experimental study. The statistical population of the study included all the women heading households supported by Imam Khomeini Relief Committee in Rasht in 2015-2016. Thirty women were selected from this population through convenience sampling and were randomly assigned to the experimental (15 individuals) and control group (15 participants). The experimental group underwent 8 sessions of prayer training. Cohen et al.'s perceived stress questionnaire was used for data gathering. The collected data were analyzed by covariance statistical method. All ethical issues were observed in the study and the researchers declared no conflict of interests. Results: The findings indicated that women in the experimental group had a significantly lower level of stress than their counterparts in the control group. Thus, the research hypothesis (i.e. prayer training is effective in reducing perceived stress among women heading households) was confirmed (p<0.01). Conclusion: Taken together, prayer training has a significant effect on declining perceived stress of women heading households. For downloading the full-text of this article please click here. Please cite this article as: Sheykholeslami A, Parsa M. The Effectiveness of Prayer Training on Perceived Stress of Women Heading Households Supported by Imam Khomeini Relief Foundation.J Res Relig Health. 2019; 4(5): 17- 26.